Cyber Physical System: The Role of Website as a Medium of Digital Marketing for Ecotourism - Ina Primasari; Sri Herwindya Baskara Wijaya; Henricus Hans Setyawan Prabowo; Joko Suranto (Postgraduate, University of Mataram, 2023)
The advancement of human civilisation and the development of the global economy in various fields has now entered Indonesia with various new digital-based technologies and is currently known as the industrial era 4.0 which is based on cyber physical systems. Digitalisation in various fields is currently also intensively carried out in the tourism sector which is one of the country's foreign exchange boosters. Indonesia's tourism development is supported by adequate human resources and the diversity of natural resources which is an added value in order to sedate tourists to visit tourist destinations in Indonesia. The tourism village will later become an independent tourism village with sustainable tourism village certification. The assistance is carried out through the development of Human Resources in the management of tourist villages, product development or travel patterns, and digital development. In the management of digitalisation-based Independent Tourism Villages, the 7 destinations have used websites as a marketing communication medium. With the existence of digital technology-based marketing communication, many Tourism Villages are now increasingly recognised by the wider community across time and space. Marketing communication through websites is one of the right strategies for tourism businesses because it is a more efficient and effective media display and has a positive significance for the tourism sector.